Meningioma of the cerebellar peduncle revealed by sudden deafness: A case report - El Omri, Malika; Misbah, Linda; Bellakhdher, Mouna; Jemli, Safa; Houas, Jihene; Ghammem, Monia; Meherzi, Abir; Wassim, Kermani (Biomedicine & Healthcare Research, 2026)
Introduction: Meningiomas in adults represent the most frequent of all primary intracranial tumors in adults. Location and size of such tumors dictate their clinical characteristics. Multiple locations are extremely rare, resulting in atypical clinical presentation and complications, such as a cerebellar peduncle-based meningioma discussed in this case report, manifesting as sudden sensorineural hearing loss. We aim to discuss an exceptional etiology of sudden deafness, describing its clinical and therapeutic features in order to ensure a better understanding of meningioma of this location. Case presentation: This was a 35-year-old woman with no medical history of pathology who was admitted to our department for a sudden sensorineural hearing loss (SSNHL) in the left ear. The physical examination revealed a normal, complete eardrum on both sides, as well as a neurovestibular examination without abnormalities. Audiometry showed left cochleosis. We completed a Magnetic Resonance Imaging (MRI) of the brain and the pontocerebellar angle, which showed a meningioma next to the left cerebellar peduncle associated with vestibular signal abnormalities related to a hemorrhagic rearrangement of the meningioma. We referred the patient to neurosurgery for additional management. Clinical discussion: Sudden sensorineural hearing loss is a well-recognized clinical condition, typically idiopathic in origin. Meningiomas located outside the cerebellopontine angle are rarely implicated as a cause of hearing loss. Surgical resection of the meningioma can lead to significant restoration of auditory function. This underscores the importance of considering prompt surgical intervention in cases of SSNHL to potentially reverse hearing deficits. Conclusion: Sudden deafness is rare, and its occurrence in association with cerebellopontine angle tumors is even rarer.